2023
DOI: 10.3390/antiox12061267
|View full text |Cite
|
Sign up to set email alerts
|

Veronica persica Ethanol Extract Ameliorates Dinitrochlorobenzene-Induced Atopic Dermatitis-like Skin Inflammation in Mice, Likely by Inducing Nrf2/HO-1 Signaling

Abstract: Atopic dermatitis (AD) is chronic allergic contact dermatitis with immune dysregulation. Veronica persica has pharmacological activity that prevents asthmatic inflammation by ameliorating inflammatory cell activation. However, the potential effects of the ethanol extract of V. persica (EEVP) on AD remain elusive. This study evaluated the activity and underlying molecular pathway of EEVP in two AD models: dinitrochlorobenzene (DNCB)-induced mice and interferon (IFN)-γ/tumor necrosis factor (TNF)-α-stimulated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The unheated yuzu seed oil used in this study contained limonin, which has been shown to regulate the expression of various cytoprotective enzymes such as heme oxygenase-1 (HO-1) and NAD(P)H quinone oxidoreductase 1 (NQO1) by activating the Nrf2/ARE pathway [ 27 , 28 , 29 ]. Moreover, inducing the Nrf2/HO-1 signaling pathway inhibits inflammatory AD in skin keratinocytes [ 30 ]. Therefore, we hypothesized that limonin-containing unheated yuzu seed oil plays a regulatory role in AD via the Nrf2/ARE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The unheated yuzu seed oil used in this study contained limonin, which has been shown to regulate the expression of various cytoprotective enzymes such as heme oxygenase-1 (HO-1) and NAD(P)H quinone oxidoreductase 1 (NQO1) by activating the Nrf2/ARE pathway [ 27 , 28 , 29 ]. Moreover, inducing the Nrf2/HO-1 signaling pathway inhibits inflammatory AD in skin keratinocytes [ 30 ]. Therefore, we hypothesized that limonin-containing unheated yuzu seed oil plays a regulatory role in AD via the Nrf2/ARE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to severe oxidative damage, cells activate an antioxidant protection network organized by key regulatory factors including nuclear factor erythroid 2-related factor (Nrf2) and heme oxygenase-1 (HO-1) [39,40]. Activation of the Nrf2/HO-1 pathway alleviates AD-like symptoms [41][42][43]. The activation of the Nrf2/HO-1 pathway induces the expression of antioxidant enzymes and aims to restore redox homeostasis [44].…”
Section: Introductionmentioning
confidence: 99%